Dietary fiber and health - Cho, Sungsoo; Almeida, Nelson (CRC Press, 2012)
"Preface Fiber offers a variety of health benefits and is essential to reduce the risk of such chronic diseases as diabetes, obesity, cardiovascular disease, and diverticulitis. According to the Institute of Medicine (IOM), adequate intake (AI) of total fiber should be 14 g/1000 kcal. The IOM recommendation is joined by those from a variety of government public health agencies that promote increased fiber consumption, but a majority of people in developed countries still fall short of recommended values. On average, Americans consume only half of required intake, and approximately 90% of the U.S. population fails to meet AI goals. The problem stems largely from the fact that most conventional high-fiber foods are not tasty. Their organoleptic properties lack the kind of sensory attributes that people seek in the foods they eat. This makes it imperative for food companies to formulate tasty foods with high fiber content to improve population-wide consumption. Many have done so with new fiber ingredients that satisfy consumer demands while also delivering the health benefits of fiber. This book discusses findings from the Ninth Vahouny Fiber Symposium, which was held in Bethesda, Maryland, in June 2010. It includes a definition of fiber developed through expert consensus and delves into the many health benefits of fiber, including its prebiotic effects and roles in weight management, glycemic control, cardiovascular health, and intestinal regularity. It also reviews a variety of fiber ingredients that can be used in many appealing foods. The book provides details of claim opportunities for fiber ingredients and fiber-containing foods as well as a list of global suppliers of these ingredients. It is designed for use by food product developers, nutritionists, dietitians, and regulatory agencies"--Provided by publisher.
Keywords: Fiber in human nutrition -- Therapeutic use.; Fiber in human nutrition.; elektronické knihy; electronic books